PENDEKATAN INTERPESONAL DALAM PEMBELAJARAN INTERAKTIF - Gadis, Gadis Putri Sakinah; Irawati Tarihoran; Wisnu Fadillah; Abdul Fattah Nasution (Cendekia Madani Nusantara, 2024)
The research was conducted regarding the close relationship between a student, namely the teacher, and his students. In the teaching and learning process, it is necessary to approach students so that they are willing to listen to the aims and objectives conveyed by the teacher. The approach process used is not easy, a teacher must master the students he is teaching and how the teacher can channel the positive impacts that will occur. In this approach, communication is very necessary. For this reason, a teacher’s interpersonal communication must be able to bring students to a critical mindset, a way of communicating with other people, and being able to master the lesson. With open communication between teachers and students, students will feel cared for and can be open about things that are considered important to discuss. In terms of approach, communiacation is very important and is even the main factor in an approach. Good communication can create a good relationship with the perpetrator. Communication aims to build relationships between teachers and students, building a sense of trust, mutual openness, and so on. Interpersonal relationships in interactive learning have an important role in increasing students enthusiasm for learning. Therefore, interpersonal relationships in interactive learning are very important to encourage students learning abilities to achieve maximum learning goals